Impact of corporate taxation on unemployment - Zirgulis, Aras; Šarapovas, Tadas (Journal of Business Economics and Management, 2017)
We study the effect of corporate taxation on unemployment utilizing a dynamic panel covering 41 countries over 11 years. The purpose of this article is to investigate how changes in the corporate income tax affect unemployment. We employ system general method of moments (GMM) due to peculiarities of the data set and the endogeneity issues present in the research problem. We find that a rise in the effective average corporate tax rate significantly increases unemployment levels, which directly contradicts past findings of some seminal authors. In addition, the present research supports findings of past studies on capital tax elasticity that obtained similar insights using differing methodologies. This research lays the groundwork for future studies, which may take the same methodology and apply it to even larger international panels. This research implies that international tax competition is affecting unemployment, presumably through its effects on international capital investment. These results provide support for policy makers who may be wary of raising corporate tax rates in countries where capital is especially mobile because of the negative effects which may accumulate to the voting public in the form of unemployment.